Effect of seriphium plumusom meal inclusion in diets on productivity, carcass characteristics, methane production and emission by Nguni Steers - Phoko, Motswapo Esther (My University, 2023)
Rangeland contribute about 70% of the feed that sustain livestock throughout the year. However, due its degradation arising from among others woody plant encroachment, a shift of savanna and grassland biomes to closed woodlands reduces herbaceous productivity and economic benefits of rangelands to livestock. Woody plant encroachment (also called bush encroachment, bush thickening, shrub invasion) is a natural phenomenon characterised by the increase in woody plant density at the expense of the herbaceous layer. Bush thickening predominantly occurs in grasslands, savannas and woodlands and can cause biome shifts from open grasslands and savannas to closed woodlands. The aim of this study was to determine the effect of Seriphium plumosm meal inclusion levels in diets on feed intake, growth performance and digestibility, methane emission and meat quality of Nguni steers. The trial was conducted at the Agricultural Research Council – Animal production, feedlot for 111 days (i.e. 21 days of acclimitazation followed by 90 days of actual data collection). Twenty-eight Nguni steers, aged 22-months, with a body weight of 300kg ± 10 kg, were assigned to four treatment diets containing 0, 10, 20 or 30% of S. plumosum meal, replicated four times with seven steers per replicate in a complete randomized design. The diets were isocaloric and isonitrogenous and formulated to meet nutritional requirements of growing steers. Animal performance (average daily intake, feed conversion rate, growth performance) were measured, while digestibility trial was conducted following the total faecal collection method. Methane emission was measured using a laser methane detector technique and the bacterial population was investigated by DNA profiling using 16S rRNA gene with Illumina MiSeq. The mineral concentration (calcium, phosphorus, sodium, potassium) in rumen fluid were determined by Perkin Elmer Model Optima 7000 DV spectrometer. Carcass (dressing percentage, eye muscle area and back fat thickness) and meat quality traits (meat colour, sarcomere length, myofibril fragmentations lengths, collagen solubility, drip loss, water holding capacity, lipid and protein oxidation) were sampled and analysed following the commercial abattoir practices at the ARC – AP abattoir. A trained panel evaluated the sensory attributes (taste, aroma, flavour and texture properties) while tenderness was determined by using Warner Braztler blade. Data was analysed using General Linear Model (GLM) of SAS version 9.4. Seriphium plumosm meal inclusion levels in the diet did not (P>0.05) affect dry matter intake, body weight gains and feed conversion ratio. However, S. plumosum meal inclusion in the diet improved (P<0.05) neutral detergent fibre digestibility, carcass dressing percentage and myofibril fragment length of Nguni steers. Digestibility of neutral detergent fibre and carcass dressing percentage significantly improved (P<0.05) at 10% of S. plumosum inclusion, whereas, myofibril fragment length improved (P<0.05) at 30% S. plumosum meal inclusion in a diet. Inclusion of S. plumosum meal in diet significantly (P<0.05) reduced enteric methane emission. The meat sensory attributes were not affected (P>0.05) by the diets. It was concluded that S. plumosum meal inclusion levels used in the study reduced methane emission by Nguni steers, and did not cause any adverse effects on animal perfomance. However, further long-term studies are recommended to ascertain these findings.
Thesis (Ph. D. (Animal Production)) -- University of Limpopo, 2023
Keywords: Animal performance.; Beef quality.; Forage quality and quantity.; Greenhouse gases.; Woody plant encroachment.; Invasive plants -- South Africa -- Biological control; Sorghum as food; Nguni cattle; Beef cattle -- Feeding and feeds